Universal, International and National Components of the Paremiological Stock of the Modern Belarusian (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
system of modern Belarusian language is differentiated into three multilingual types: binational (it is limited by the contact between two languages), international (it is caused by the contacts between more than two languages) and proper universal (it is not caused by the language contacts). The most productive is the international component, the least – proper universal. National component of the Belarusian paremiological system is differentiated into culturally determined one (proper Belarusian) and culturally marked variants of universal proverbs in the Belarusian language.The culturally marked variants are common to all kinds of universal units (the variants of binational proverbs prevail). Universal proverbs predominate among the paremiological units used in the texts of the informational style (more than 75%). The national component mainly consists of culturally marked variants of universal proverbs. The universal paremiological units also prevail in the texts of journalistic style (about 55%). The national component is almost equally represented by culturally determined proverbial units and culturally marked variants of universal proverbs. On the whole, the proper universal component of the Belarussian paremiology is less than the proper national component (approximately twice a large). Such proportion is caused by the large productivity of culturally marked variants of universal proverbs in the paremiological system of modern Belarusian language. This fact proves the high degree of national and cultural determination of the paremiological stock of the Belarusian language.
Keywords: Modern Belarusian; Paremiological Stock; Universal; International; National